UTILIZATION OF HERBAL BY THE JAMBI MALAY TRIBE IN INDONESIA IN THE STUDY OF ETHNOBOTANY (Jurnal Bioconcetta, 2021)
ABSTRACTThis study documents the use of leaves used by the Jambi Malay Tribe, Indonesia. The research method used is descriptive survey method. Samples were taken at simple random (Simple Random Sampling) with roaming method. Prior to sampling, interviews were conducted with the RRA (Rapid Rural Appraisal) approach and with direct observation of medicinal plant species found in the field. The results of identification and interviews obtained 57 types of herbal plants. From Class Dicotyledoneae 51 types of leaves and 6 types of leaves from Class Monocotyledoneae are used as herbs. The species with the most medicinal properties is Piper betle L. (three diseases)